Differentiation of Type 2 Autoimmune Pancreatitis Presenting as Clinical Acute Pancreatitis - Tae Hoon Lee (Gut and Liver, 2019)
Background/AimsMetallic stents designed to relieve malignant biliary obstruction are susceptible to occlusive tumor ingrowth or overgrowth. In a previous report, we described metallic stents covered with paclitaxel-incorporated membrane (MSCPM-I, II) to prevent occlusion from tumor ingrowth via antitumor effect. This new generation paclitaxel-eluting biliary stent is further endowed with sodium caprate (MSCPM-III) for enhanced drug delivery. The purpose of this study is to examine the safety of its drug delivery system in the porcine biliary tract.Methods : MSCPM-III (10% [wt/vol] paclitaxel) and covered metal stents (CMSs) were endoscopically inserted in porcine bile ducts in vivo. Histologic biliary changes, levels of paclitaxel released, and various serum analytes (albumin, alkaline phosphate, aspartate transaminase, alanine transaminase, total protein, total bilirubin, and direct bilirubin) were assessed.Results : Based on the intensity of reactive inflammation and fibrosis, changes in porcine biliary epithelium secondary to implanted MSCPM-III were deemed acceptable (i.e., safe). Histologic features in the MSCPM-III and CMS groups did not differ significantly. In a related serum analysis, paclitaxel release from MSCPM-III stents was below the limit of detection for 28 days. Biochemical analyses were also similar for the two groups, and no evidence of hepatic or renal toxicity was found in animals receiving MSCPM-III stents.Conclusion : sIn a prototypic porcine trial, this newly devised metal biliary stent incorporating both paclitaxel and sodium caprate appears to be safe in the porcine bile duct.